Pengaruh model bisnis canvasing terhadap risiko pada industri ﬁntech P2P lending Indonesia - Mohammad Fahmi Arkanuddin; Bernardus Yuliarto Nugroho; Chandra Wijaya (Journal of Business & Banking, 2021)
This quantitative study aims to analyze the signiﬁcant effect of the application of the canvasing business model on risk. The data were analysed using structural equation modeling (SEM) on 100 respondents through the distribution of questionnaires. In addition, interviews were also conducted with several P2P lending ﬁntech stakeholders to obtain an in-depth analysis of the problem. The result showed that the canvasing business model variable has a signiﬁcant effect on risk with an estimate of 0.871. The P2P lending ﬁntech industry has an inherent risk, namely credit risk and there are 7(seven) components of the canvasing business model (CBM) that have a correlation to credit risk and the risk of the COVID-19 pandemic. Credit risk due to NPL caused by unbanked and underserved can be mitigated by implementing the CBM components and the customer segments. The application of customer segments and keys of partnership can mitigate fraudster. Over debt can be mitigated by the application of a key of partnership. Meanwhile, the risk of pandemic-covid 19 is one type of risk that is added for research in addition to 8 (eight) types of risk, which can be mitigated by implement-ing one component or element of CBM. CBM is a channel, by utilizing e-channels, through the use and use of mobile applications.